Elements for a general theory of equality and non discrimination regarding European experience - Borrillo, Daniel (2013)
The article analyzes the implications of shifting from modernto a welfare state according with the definition of equality principle, then explains the consequences of promoting the non discrimination principle and its structure as surety element of free competition. On that basis, the author presents the main tools of non discrimination in European law and then gives details about three components of discrimination: “tracto, criterium and spatium”. Finally, the article explores the debate surrounding the notion of evidence when it is related to discrimination, emphasizing States duty on promoting equality in European law.